Biomechanics, exercise physiology, and the 75th anniversary of RQES - Hamill, J.; Haymes , E. M. (Research Quarterly for Exercise and Sport, 2004)
The purpose of this paper is to review the biomechanics and exercise physiology studies published in the Research Quarterly for Exercise and Sport ( RQES ) over the past 75 years. Studies in biomechanics, a relatively new subdiscipline that evolved from kinesiology, first appeared in the journal about 40 years ago. Exercise physiology studies have been published in RQES throughout its history. Studies in both subdisciplines reflect areas of research that were of great interest at the time of their publication. Many of the leading scholars, past and present, in both biomechanics and exercise physiology were authors of papers in RQES.